2024
DOI: 10.1038/s41419-024-06569-x
|View full text |Cite
|
Sign up to set email alerts
|

OTUD4 promotes the progression of glioblastoma by deubiquitinating CDK1 and activating MAPK signaling pathway

Mingxin Ci,
Gaichao Zhao,
Chongyang Li
et al.

Abstract: Glioblastoma, IDH-Wild type (GBM, CNS WHO Grade 4) is a highly heterogeneous and aggressive primary malignant brain tumor with high morbidity, high mortality, and poor patient prognosis. The global burden of GBM is increasing notably due to limited treatment options, drug delivery problems, and the lack of characteristic molecular targets. OTU deubiquitinase 4 (OTUD4) is a potential predictive factor for several cancers such as breast cancer, liver cancer, and lung cancer. However, its function in GBM remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Notably, recent findings have shown that OTUD4 is overexpressed in glioblastoma, a highly aggressive primary malignant brain tumor. In this context, OTUD4 plays a crucial role in cell proliferation, invasion, and clonogenic capacity by deubiquitinating CDK1 and activating the MAPK signaling pathway ( 15 ).…”
Section: Overcoming Immunosuppressive Tumor Microenvironment In Breas...mentioning
confidence: 99%
“…Notably, recent findings have shown that OTUD4 is overexpressed in glioblastoma, a highly aggressive primary malignant brain tumor. In this context, OTUD4 plays a crucial role in cell proliferation, invasion, and clonogenic capacity by deubiquitinating CDK1 and activating the MAPK signaling pathway ( 15 ).…”
Section: Overcoming Immunosuppressive Tumor Microenvironment In Breas...mentioning
confidence: 99%